If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X(9x + -4) = (9x + 6)(x + -1) Reorder the terms: X(-4 + 9x) = (9x + 6)(x + -1) (-4 * X + 9x * X) = (9x + 6)(x + -1) (-4X + 9xX) = (9x + 6)(x + -1) Reorder the terms: -4X + 9xX = (6 + 9x)(x + -1) Reorder the terms: -4X + 9xX = (6 + 9x)(-1 + x) Multiply (6 + 9x) * (-1 + x) -4X + 9xX = (6(-1 + x) + 9x * (-1 + x)) -4X + 9xX = ((-1 * 6 + x * 6) + 9x * (-1 + x)) -4X + 9xX = ((-6 + 6x) + 9x * (-1 + x)) -4X + 9xX = (-6 + 6x + (-1 * 9x + x * 9x)) -4X + 9xX = (-6 + 6x + (-9x + 9x2)) Combine like terms: 6x + -9x = -3x -4X + 9xX = (-6 + -3x + 9x2) Solving -4X + 9xX = -6 + -3x + 9x2 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Reorder the terms: 6 + -4X + 3x + 9xX + -9x2 = -6 + -3x + 9x2 + 6 + 3x + -9x2 Reorder the terms: 6 + -4X + 3x + 9xX + -9x2 = -6 + 6 + -3x + 3x + 9x2 + -9x2 Combine like terms: -6 + 6 = 0 6 + -4X + 3x + 9xX + -9x2 = 0 + -3x + 3x + 9x2 + -9x2 6 + -4X + 3x + 9xX + -9x2 = -3x + 3x + 9x2 + -9x2 Combine like terms: -3x + 3x = 0 6 + -4X + 3x + 9xX + -9x2 = 0 + 9x2 + -9x2 6 + -4X + 3x + 9xX + -9x2 = 9x2 + -9x2 Combine like terms: 9x2 + -9x2 = 0 6 + -4X + 3x + 9xX + -9x2 = 0 The solution to this equation could not be determined.
| 3y+5=24+3-5 | | 2*4=8*2 | | 100=36+4s | | X=3.8+-.6*6.33+-1.66x | | 10p-3=(12+4p)-7 | | p-26=5*4 | | (x+11)+(2x+8)+(3x+1)=180 | | -5(w+6)=4w+15 | | x+11+2x+8+3x+1=180 | | -18g-(-7g)+19g-6g=14 | | 5x-8x+2=9x+1 | | 20=8+a*4 | | 12w+10=2w | | 1/4(y-8)=12 | | 5u-14=2(u-4) | | -12x+7x-63=42 | | 20/x=1.618 | | 36+47=111-z | | Y=10log(x) | | 4w-w=45 | | 1x+1x-7.50+1x-12=63 | | 4.43(k-19)=4.43 | | -4=14.76/s | | N+54=45 | | 3(c+1.46)+2.12=19.97 | | 9/10x-9/10=4 | | 2(z+1.5)=9.8 | | 3.1(d-6)+1=7.2 | | B+50=35 | | 21+3x=-y | | -21(t+683)=840 | | 5x+10=2x-20 |